2021
DOI: 10.3390/healthcare9060760
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Diagnosis and Therapy of Infective Endocarditis in Children and Adolescents—Cohort Study

Abstract: Despite the progress in management and prophylaxis measures, infective endocarditis (IE) is still a condition associated with high mortality rates and severe complications. Fortunately, the incidence of IE is much lower in children and adolescents, with only 0.05–0.12/1000 cases being reported in hospitalized pediatric patients. According to recent data, IE is, in most cases, a complication of pre-existing congenital heart disorders, in up to 75–90% of cases. About 8–10% of all IE cases occur in children witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Fungal endocarditis is a rare disease that occurs in patients with predisposing factors. It mainly occurs in immunocompromised patients who have received broad-spectrum antibiotic therapy and have heart valve replacement and/or pacemakers [19][20][21]. In our study, fungal IE was detected in a patient with a catheter followed up for rhabdomyosarcoma and receiving active chemotherapy.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Fungal endocarditis is a rare disease that occurs in patients with predisposing factors. It mainly occurs in immunocompromised patients who have received broad-spectrum antibiotic therapy and have heart valve replacement and/or pacemakers [19][20][21]. In our study, fungal IE was detected in a patient with a catheter followed up for rhabdomyosarcoma and receiving active chemotherapy.…”
Section: Discussionmentioning
confidence: 51%
“…Although blood cultures have a very important place in both the diagnosis and treatment of IE, 5-68% of patients had negative blood cultures. It has been reported that the reasons for this are the use of antibiotics before culture taking, infections caused by slow-growing microorganisms, or the use of inadequate microbiological techniques [ 7 , 20 - 23 ]. In our study, 38% of patients had negative blood cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 50–70% of pediatric IE is seen in patients with congenital heart disease [ 7 , 8 , 9 ], which is the main predisposing condition. Conversely, in adult patients, the most common heart diseases predisposing to IE include degenerative valve disease or valve replacement surgery with prosthesis implantation, which are significantly more common than in children [ 10 ].…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Some examples are those with immunodeficiency, patients with frequent invasive interventions or with central catheters (chemotherapy, nutrition, or haemodialysis), and institutionalized patients [ 8 ]. Children with cancer present several concurrent risk factors, such as tumor-related immunosuppression, nutritional deficit, chemotherapy, and the placement of catheters and central vascular accesses [ 7 , 18 , 19 ]. The frequency of IE in this group has increased substantially in recent years and the rise in cases will probably continue in the next coming years as the survival of pediatric cancer keeps improving.…”
Section: Predisposing Factorsmentioning
confidence: 99%